Proteomics of physiologically relevant stresses on model mycobacterium tuberculosis organisms, and the effects on virulence - Ganief, Muhammad (Department of Human Biology, 2024)
In 2020 approximately 10 million people suffered from tuberculosis and it is estimated that 1.5 million died. Mycobacterium tuberculosis which is the causative agent of tuberculosis disease, is an obligate aerobic bacterium with a unique cell wall and is capable of surviving and infecting a immunocompetent host. The bacteria are spread by aerosols, where an infected individual coughs to release bacteria that are inhaled by new potential hosts. As a result Mycobacterium tuberculosis travels through the respiratory tract, where it makes first contact with the host immune system. Alveolar macrophages are thought to be the primary site of initial infection, and Mycobacterium tuberculosis can replicate within these cells, and withstand the various environmental challenges this entails. In this work, we use liquid chromatography coupled high resolution tandem mass spectrometry (LC-MS/MS) based proteomics, to study some of the environmental challenges that Mycobacterium tuberculosis may encounter within the host, in the model organisms Mycobacterium smegmatis and Mycobacterium bovis BCG. These include sub-lethal concentrations of nitric oxide and hydrogen peroxide, cholesterol as a carbon source, as well as nitric oxide in a background of cholesterol as a carbon source. We also performed LC-MS/MS based proteomics to probe the temporal host response to Mycobacterial infection, using murine macrophage cell models of both circulating and alveolar macrophages. In addition to LC-MS/MS based proteomics, we also performed infection assays to determine if exposure to the aforementioned environmental stressors alter the survival of Mycobacteria in macrophages. In this work, we show that pre-exposure to nitric oxide or hydrogen peroxide increases the survival of Mycobacterium smegmatis in RAW264.7 macrophages, and this is correlated with the activation of the DosR regulon. In Mycobacterium smegmatis, proteomic changes suggest that the lipidome of Mycobacteria may play a role in enhanced survival in macrophages. In Mycobacterium bovis BCG exposed to nitric oxide at sub-lethal doses in a background of cholesterol metabolism, does not confer enhanced survival in alveolar like MPI macrophages, but does enhance bacterial uptake, which has implications for bacterial dissemination. Much like in Mycobacterium smegmatis, these changes are associated with the activation of DosR regulon. From proteomics data we generated from Mycobacterium bovis BCG, when compared to transcriptomic data from Mycobacterium tuberculosis H37Rv shows that cholesterol metabolism, and the wider adaptations associated with cholesterol metabolism are key features of intracellular life. These wider adaptations to cholesterol metabolism include protection against metal toxicity and starvation, and several virulence factors were also found to be differentially expressed. In addition to the bacterial response to intracellular environmental stressors, we also studied the host response to infection. We observe that alveolar-like MPI cells are more permissive to infection, and are less able to control the infection compared to the RAW264.7 cells which are models of circulating macrophages. These observations may be due to impared endocytic trafficking in MPI cells and the greater expression of phagocytic receptors. The cell types may also differ in cytokine signaling and antigen presentation, which have implications for T-cell mediated cytotoxicity. Taken together, our work suggests that exposure to host-environmental stressors induce the adaptation of Mycobacteria to the host-cell environment, and further that this adaptation may have further implications in dissemination of bacteria. Further, our work also demonstrates that cell-type specific host-responses may have relevant implications for immune signaling and trafficking.